PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI DALAM MEMPENGARUHI KINERJA GURU DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Masarif, Ananda Fibiola; Karnadi, Karnadi; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The impact of leadership approach and organizational culture on shaping teacher performance, with work discipline serving as an intervening variable Human Resource Management stands as a field that focuses on efficiently and effectively managing the interactions and roles of resources, namely the workforce, possessed by individuals. The aim is to utilize these resources optimally to attain the objectives of educational institutions. The primary goal of this study is to ascertain whether variables like Leadership Style, Organizational Culture, and Work Discipline exert a significant or insignificant impact on the performance of both Civil Servant (ASN) and Non-Civil Servant (Honorary) Teachers at SMP Negeri 3 Situbondo. The research methodology involves assessing validity, testing reliability, evaluating classical assumptions, measuring goodness of fit (GOF), and calculating the coefficient of determination The research findings reveal that the convergent validity test results indicate X1 = 0.625, X2 = 0.687, Y1 = 0.640, Y2 = 0.698. The reliability test outcomes show X1 = 0.798, X2 = 0.848, Y1 = 0.810, Y2 = 0.891. The classical assumption test demonstrates that the independent variables X1, X2, Y1 influence each other in a manner where the Variance Inflation Factor (VIF) values are all below 5.00. The goodness of fit (GOF) test results confirm that the values of Standardized Root Mean Square Residual (SRMR), Chi-Square, and Normed Fit Index (NFI) meet the criteria, with the model's significance level being 0.592 (p > 0.05). The test for the coefficient of determination indicates that the combined impact of Variables (X1) and (X2) on Work Discipline (Y1) accounts for 41.7% of the variation, leaving 58.3% influenced by other unexamined factors. Similarly, (X1) and (X2) together influence (Y2) by 60.8%, with the remaining 39.2% being influenced by variables not covered in this